2012
DOI: 10.1590/s0004-282x2012001100009
|View full text |Cite
|
Sign up to set email alerts
|

Early stroke case-fatality rates in three hospital registries in the Northeast and Southeast of Brazil

Abstract: Few studies have addressed early cerebrovascular lethality in Brazil. OBJECTIVE: To evaluate 10 and 28-day stroke case-fatality rates in three hospitals in three Brazilian cities. METHODS: We described the stroke registries in São Paulo, João Pessoa, and Natal. RESULTS: Out of a total of 962 first-ever events (mean age, 68.1 years-old; 53% men), 83.6% (804 cases) were classified as ischemic and 16.4% (158) as hemorrhagic stroke. Overall, the case-fatality rates and 95% confidence intervals (95%CI) for hemorrha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
1
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
1
7
1
5
Order By: Relevance
“…In two other crosssectional, hospital-based studies conducted during 2001 and 2006-2008 in Qom, a well-known religious city of Iran, the casefatality rate within the first month was reported at 24.6% during 2001, and at 15.3% from 2006 to 2008. Although, these figures showed an apparently declining rate over time in this region, but were still greater than reported ones from western countries and lesser than other developing countries [8][9][10][11][12].…”
Section: Introductioncontrasting
confidence: 60%
“…In two other crosssectional, hospital-based studies conducted during 2001 and 2006-2008 in Qom, a well-known religious city of Iran, the casefatality rate within the first month was reported at 24.6% during 2001, and at 15.3% from 2006 to 2008. Although, these figures showed an apparently declining rate over time in this region, but were still greater than reported ones from western countries and lesser than other developing countries [8][9][10][11][12].…”
Section: Introductioncontrasting
confidence: 60%
“…It is suggested that the low hospital assistance of these FU may be the source of such stability or even low quality of the SIH/ SUS in the state health system. In general, Fernandes et al 37 verified the non-existence of mortality by stroke among hospitals in Northeast and Southeast Brazil.…”
mentioning
confidence: 96%
“…This cohort was the first one to demonstrate the prognosis value of multimorbidity using CCI in long-term survival in a stroke cohort in Latin America. EMMA study is an ongoing stroke cohort, which demonstrated several stroke outcomes mentioned in previous publications in the last decade [10,23,29,30,31,32]. The study population in EMMA comes from a low-income area with poor public health support in the city of São Paulo located in Brazil.…”
Section: Discussionmentioning
confidence: 99%